Study of Surface Temperature Monitoring in the Field of Buildings - Slávik, Richard; Čekon, Miroslav (Elsevier, 2016)
Surface temperature monitoring and its aspects does have not only a useful merit for thermal analysis of the buildings and their direct or indirect implementation in virtual simulations, however is equally of highly relevant use for the field of building physics as primarily those of more complex analyzing concerning on specific thermal phenomena. The measuring of surface temperatures at the building envelopes by means of well-practiced commercial temperature sensors are typically applied whose attributes can successfully be employed especially for the field of thermal building performance aspects. In addition, besides of their certain own accuracy level and final implementation for instance as an input parameter into the simulation model, typical methods of their final application related to the opaque and transparent building surfaces and their contact and non-contact modes may have the significant influence. The paper presents a representative confrontation of surface temperature monitoring of several temperature sensors as finally compared with the form of their final application on standard vertical building surfaces. Three typical ways of installation are demonstrated on opaque and transparent building component under real climate conditions applying of commercial thermocouples, digital temperature and infrared sensors. Experimental measurement assemblies are proposed and introduced with aim to point out deviating indicators in the presented area. Representative in-situ measurements are performed and final comparability of sensors based on typical methods of their final installation is presented. An obtained result, both at existing and comparing types, demonstrates its application relations to the field of buildings. In spite of that, an additional confrontation based on non-contact regime as compared with contact ones reveals a feasible option directly concerning on building surface temperature measuring.

Surface temperature monitoring and its aspects does have not only a useful merit for thermal analysis of the buildings and their direct or indirect implementation in virtual simulations, however is equally of highly relevant use for the field of building physics as primarily those of more complex analyzing concerning on specific thermal phenomena. The measuring of surface temperatures at the building envelopes by means of well-practiced commercial temperature sensors are typically applied whose attributes can successfully be employed especially for the field of thermal building performance aspects. In addition, besides of their certain own accuracy level and final implementation for instance as an input parameter into the simulation model, typical methods of their final application related to the opaque and transparent building surfaces and their contact and non-contact modes may have the significant influence. The paper presents a representative confrontation of surface temperature monitoring of several temperature sensors as finally compared with the form of their final application on standard vertical building surfaces. Three typical ways of installation are demonstrated on opaque and transparent building component under real climate conditions applying of commercial thermocouples, digital temperature and infrared sensors. Experimental measurement assemblies are proposed and introduced with aim to point out deviating indicators in the presented area. Representative in-situ measurements are performed and final comparability of sensors based on typical methods of their final installation is presented. An obtained result, both at existing and comparing types, demonstrates its application relations to the field of buildings. In spite of that, an additional confrontation based on non-contact regime as compared with contact ones reveals a feasible option directly concerning on building surface temperature measuring.
Study of Surface Temperature Monitoring in the Field of Buildings
Keywords: Surface temperature; Temperature sensor; Thermocouples; Digital sensor; Infrared thermometer; Surface temperature; Temperature sensor; Thermocouples; Digital sensor; Infrared thermometer